An information voyage to Canada – the state of Québec (Fiep Bulletin - online, 2015)
Being invited by the Ministry of Education in Québec, as an “expert coming to give information and analyse a situation in order to suggest elements for the solution of certain problems” (according to the terms of the invitation) I hot a very interesting stay in Québec during which I learned very much and also took, I think, some interesting suggestions to our Canadian friends.